On the systematics of the genus Synanthedon Hübner, 1819 sensu lato (Lepidoptera, Sesiidae). Part II. Thamnosphecia Spuler, 1910 - Oleg G. Gorbunov (Acta Biologica Sibirica)
The genus Thamnosphecia Spuler, 1910 is restored from synonyms of the polyphyletic genus Synanthedon Hübner, 1819: Thamnosphecia Spuler, 1910, stat. rev. The genus includes ten Holarctic species, which superficially can be divided into two species groups, viz. “red-banded” and “yellow-banded”. A morphological description and differential diagnosis are provided. It is indicated that the host plants of the larvae of the genus are representatives of 11 botanical families.